1993
DOI: 10.1037/h0079389
|View full text |Cite
|
Sign up to set email alerts
|

Planned conception and infant functioning at age three months: A cross-cultural study.

Abstract: The conceptions of 53 American and 54 Greek infants were categorized as planned or unplanned on the basis of mothers' reports. At age three months in both cultural groups, infants in the planned category showed higher levels of cognitive processing and attachment to their mothers than did infants in the unplanned category, as shown by their differential vocal responses to mothers versus a female stranger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Surprisingly, there is very little research on whether planned conception impacts upon mothers’ representations of and interactions with their infants. An exception is a study by Roe and Drivas (1993), who reported that infants born of planned conceptions vocalized more positively when interacting with their mothers than with a female stranger, whereas unplanned infants’ vocalizations showed no such differentiation. Roe and Drivas argued that these differences indicate that plannedness affects mothers’ unconscious feelings for their infants and thus their ability to engage positively with them.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, there is very little research on whether planned conception impacts upon mothers’ representations of and interactions with their infants. An exception is a study by Roe and Drivas (1993), who reported that infants born of planned conceptions vocalized more positively when interacting with their mothers than with a female stranger, whereas unplanned infants’ vocalizations showed no such differentiation. Roe and Drivas argued that these differences indicate that plannedness affects mothers’ unconscious feelings for their infants and thus their ability to engage positively with them.…”
mentioning
confidence: 99%
“…An exception is a study by Roe and Drivas (1993), who reported that infants born of planned conceptions vocalized more positively when interacting with their mothers than with a female stranger, whereas unplanned infants’ vocalizations showed no such differentiation. Roe and Drivas argued that these differences indicate that plannedness affects mothers’ unconscious feelings for their infants and thus their ability to engage positively with them. They supported this argument with the finding that infants whose mothers were more affectionate showed a greater differential vocal response between mother and stranger (Roe, Drivas, Karagellis, & Roe, 1985).…”
mentioning
confidence: 99%
“…Thus, the emotional atmosphere during early mother-infant interaction may be particularly relevant for mutual behavioural engagement and this may explain the particular influence it exerts on DVR as a measure of infant active involvement. The psychological distance expressed by negative maternal affect and reflected by the infant's behavioural organization may have mediated low DVR in unplanned or less valued infants as reported by Roe and Drivas, 1993. The directions of relations between DVR and other infant indicators of the relationship quality turned out as expected but failed to reach statistical significance for the 23 dyads with complete data sets. DVR predicted avoidant attachment behaviour significantly for the 26 cases with data on these specific measures available (c.f.…”
Section: Discussionmentioning
confidence: 78%
“…Lamb et al, 1987). The study by Roe and Drivas (1993) indicates that at this early age, approaches by strangers seemed particularly attractive for those infants whose needs for emotional exchange were not met by their primary caretakers.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation